The influence of sports practice in children aged 6 to 7 years on physical fitness, motor coordination and executive functions. - Rafaello Pinheiro Mazzoccante; Hugo de Luca Corrêa; Ioranny Raquel Castro de Sousa; Matheus Almeida Camarâ; Gabriel de Sousa Alves; Beatriz Raquel Castro de Sousa; Frederico Santos de Santana; Aparecido Pimentel Ferreira; Gislane Ferreira de Melo, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
To compare motor coordination, aerobic fitness, body composition, attention and cognitive flexibility between sports practitioners and non-practitioners children. Participated in the study 68 children aged 6-7 years old, students of a private school. The aerobic fitness was measured using the Yo-Yo Intermittent Recovery Test - level 1 (YYIR1) adapted for children. The motor performance was measured by the körperkoordination für kinder (KTK) test, composed of four tasks: balance beam, monopedal jump, transfer on platforms and lateral jumps. Cognitive flexibility and attention were assessed by the attention cancellation test (ACT) (selective attention), trail making test A (sustained attention) and trail making test B (cognitive flexibility), both of which were composed by visual search task. Sports practitioners had higher scores than non-sports practitioners children (p <0.01) in YYIR1 performance (463.9±349.3 vs 221.17±138.5); motor coordination (343.3 ± 38 vs 309 ± 21.3), lower limb thrust force (jump to 90º (18.6 ± 4.6 vs 16.1 ± 4) and jumping countermovement (19.6 ± 4 .5 vs 16.5 ± 4.1); trail making test A (107.9 ± 7.9 vs 99.3 ± 19.6) and cognitive flexibility (116 ± 15.8 vs. 106.7 ± 17.1) variables. It is possible to observe through the results a possible influence of the sports practice concerning the development of aerobic, motor, sustained attention and cognitive flexibility